Alternative Learning Media Pre Reading Ability - Masyunita Siregar (Department of Early childhood Education, 2019)
The ability to read early is an important ability given to children. Through reading skills, children will be able to gain other knowledge. Learning media is a tool for delivering material and facilitating learning activities. Learning to procure media to improve the ability to read the beginning that is appropriate for children's development is very necessary. Wrong-name learning media is one of the new media alternatives to improve initial reading skills. The purpose of this article is to add learning media to request the ability to read the beginning. And to add to the literature about the ability to read the beginning.